2020
DOI: 10.1039/c9cp04610k
|View full text |Cite
|
Sign up to set email alerts
|

Critical nucleus of Greek-key-like core of α-synuclein protofibril and its disruption by dopamine and norepinephrine

Abstract: Protofibrillar trimer is the critical nucleus for the αS fibril formation, and the tetramer is the minimal stable nucleus. The interactions of DA/NE with αS trimer/tetramer disrupt the backbone H-bonds and destabilize the αS protofibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 63 publications
4
24
0
Order By: Relevance
“…Therefore, we choose tetramer as the model of Aβ 42 protofibril in our simulation in order to save computational resources. Moreover, using the same strategy, Zou et al found that the trimer is the critical nucleus of αS 44–96 protofibril and tetramer is the smallest protofibril nucleus; hexamer is the critical nucleus and octamer is the smallest stable nucleus for the fibril of C-terminal fragment of SOD1­( 147 GVIGIAQ 153 ) …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we choose tetramer as the model of Aβ 42 protofibril in our simulation in order to save computational resources. Moreover, using the same strategy, Zou et al found that the trimer is the critical nucleus of αS 44–96 protofibril and tetramer is the smallest protofibril nucleus; hexamer is the critical nucleus and octamer is the smallest stable nucleus for the fibril of C-terminal fragment of SOD1­( 147 GVIGIAQ 153 ) …”
Section: Resultsmentioning
confidence: 99%
“…The inhibition probably activates through direct binding with the peptides and/or interfering with π–π stacking interaction between aromatic rings of amyloidogenic residues according to the observation via microscopic and quantum chemical analyses . Interestingly, some natural compounds such as taxanthin, brazilin, curcumin, dopamine, EGCG, ,, resveratrol, , and rosmarinic acid can simultaneously target the proteins involved in AD, PD, T2D, and ALS where all experimental and computational studies are reported in Table . Interestingly, although the inhibitory mechanisms of these ligands to the diseases are probably different, they all adopt a similar binding pose to Aβ peptides, α-synuclein, hIAPP, insulin, and SOD1 via molecular docking simulations (Figure ).…”
Section: Ad Pd and T2d Therapiesmentioning
confidence: 99%
“…Here, x and y refer to the number of H-bonds and radius of gyration (Rg) of PHF6* oligomers, respectively. A contact is defined when two carbon atoms or a carbon atom and another heavy atom of two non-sequential residues lie within 0.54 nm, or any other two heavy atoms of two non-sequential residues come within 0.46 nm ( Zou et al, 2019 ; Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%